Evolução molecular e padrões de expressão de genes da família das proteínas ligantes a odores (OBPs) em duas espécies de moscas-das-frutas do grupo Anastrepha fraterculus - Campanini, Emeline Boni (2016)
Odorant-binding proteins (OBPs) are of great importance for survival and reproduction since they participate in initial steps of the olfactory signal transduction cascade, solubilizing and transporting chemical signals to the olfactory receptors. A comparative analysis of OBPs between closely related species may help explain how these genes evolve and are maintained under natural selection and how differences in these proteins can affect olfactory responses, and consequently lead to species differentiation. We studied OBP genes in the closely related species Anastrepha fraterculus and Anastrepha obliqua, which, albeit generalists, have different host preferences, using transcriptomes and real time quantitative PCR data. We identified 24 different OBP sequences from Anastrepha fraterculus and 25 from A. obliqua, which correspond to 21 Drosophila melanogaster OBP genes. Phylogenetic analysis separated Anastrepha OBPs sequences in four branches that represent four subfamilies: classic, minus-C, plus-C and dimer. We found evidence of positive selection in three classic subfamily genes OBP56h-1, OBP56h-2 e OBP57c and in the plus-C subfamily gene OBP50a, and at least one duplication event that preceded the speciation of these two species. Four positively selected sites putatively resulted in radical changes in amino acid properties. Inferences on tertiary structures of putative proteins from these genes revealed that at least one positively selected change involves the binding cavity (the odorant binding region) in the plus-C OBP50a, which is important because changes in the binding cavity could change OBPs specificity. Differential gene expression analysis at different reproductive stages showed that all nine OBP genes tested were significantly differentially expressed between A. fraterculus and A. obliqua at several reproductive profiles, but OBP56a, OBP56d, OBP57c and both OBP56h paralogs showed the highest differences in expression levels. The results generated in this study indicated that at least seven OBP genes may be involved in the A. fraterculus e A. obliqua differentiation, and in the fraterculus group differentiation as well.